Pengujian Aplikasi Penjualan Berbasis Web Menggunakan Black Box dengan Teknik Boundary Value Analysis - Ubaydillah; Christiandrew Tjahja; Edi Setiawan; Gilang Noor Cahyo; Aries Saifudin (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
In software testing, validation is the process of checking whether the software meets the desired criteria. The data validation process that is less than the maximum can create a discrepancy in the data that will be saved to the database. For example, the amount of data entered may exceed the expected limit. This can be detrimental to application owners and users. So it is necessary to improve the quality of better validation, in order to help users in terms of data accuracy. Applications made must pass the testing phase to ensure the quality of the software. The proposed method used to test the quality of the application this time is the black box method with boundary value analysis techniques. The boundary value analysis technique is used to determine the lower and upper limit values ​​of the data to be tested, which are considered suitable for testing sales applications at Raja Retail Stores. The steps taken in this research are starting from identifying the problem, selecting test data, entering test data into the system, carrying out the testing process using Boundary Value Analysis techniques, calculating test data, and closing with documentation of test results. Based on the results of the tests carried out, it can be concluded that the sales application at Raja Retail based on the website tested can run well as desired by the user, in terms of form functions and database functions. Validation can be done well without having to worry about errors.